(untitled) (Revista de História Regional, 2007)
The study of the organization of the rural workers fight starting from their experiences. This daily fight which has happened in Goiás since the capitalist rural expansion, culminating with a process of rural social exclusion. In these considerations they are agglutinated around the debates on the expansion front and pioneering front. Consolidated in the fights for land, for labor laws, for health, for improvement of human life living in rural parts of the country. The case study of the resistances and the rural workers of Itapuranga fights - 1970-80.